Perancangan Papan Informasi Digital Berbasis Web pada Raspberry pi - Rizal Panuntun; Adian Fatchur Rochim; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Digital signage is information boards migrate from conventional forms to digital form. Form of digital signage used in computer by connecting to monitor to display the information. Digital notice board (digital signage) puts a digital-based information services in one direction. Many digital signage applications appear with the development of information technology. Unfortunately, if used as a digital signage devices, the implementation of existing digital signage applications using a desktop computer is unefficient. Signage applications that developed to be implemented on a single board computers such as raspberry-pi is still rare. In that case, there are any idea to implement a mini computer raspberry-pi as digital signage devices. Mini computer raspberry-Pi was chosen because of its small size and power saving. so it can be efficient and flexible than a regular desktop computer. Forming of this thesis includes designing web server using PHP and MySQL and raspberry pi configuration. The results of this research is to implement digital signage in raspbeery pi that produce a web-based digital information boards that efficient and power saving.